The relationship between growth and stand density of Eucalyptus grandis (Hill) Maiden - Bredenkamp, Brian V.(Brian Victor) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1977.